THE FEATURES OF SEIZURES WHICH OCCUR AS THE RESULT OF A TRAUMATIC BRAIN INJURY IN THE PATIENTS WITH CHIARI MALFORMATION TYPE I - M. R. Yarmukhametova (Эпилепсия и пароксизмальные состояния, 2016)
The traumatic brain injury (TBI), hypoxia, structural brain abnormalities are important causative factors for development of epilepsy. Posttraumatic epilepsy (PTE) is estimated to constitute 5% of all cases of epilepsy and over 20% of cases of symptomatic epilepsy. Objective of this study was to explore the seizure types in the patients with Chiari malformation type I which occur as the result of TBI. It is revealed that the patients with Chiari malformation had primary generalized seizures. Probably, such result associate with provocative role of TBI. None of the patients with Chiari malformation type I had early posttraumatic seizures, this fact we explain they didn’t have very severe TBI in anamnesis.